Integrasi Prinsip Arsitektur Berkelanjutan dan Tata Ruang Tropis pada Desain Kafe Perkotaan: Studi Kasus Tanatap Wall Garden Semarang - Mutiara Fajar Sholehah; Zakiyah Wardah Isfahani (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the integration of sustainable architecture principles and tropical spatial planning in the design of an urban café through a case study of Tanatap Wall Garden Semarang. The research employs a qualitative descriptive method with a case study approach, supported by field observations, spatial analysis, and literature review. The findings reveal that sustainable design strategies are implemented through passive design approaches, including natural ventilation, optimal daylight utilization, climate-responsive spatial zoning, and the extensive use of bioophilic elements. Tropical spatial planning is reflected in the transition between outdoor, semi-open, and indoor spaces, which enhances thermal comfort and reduces reliance on mechanical systems. These design strategies not only improve environmental performance but also shape visitors’ spatial experience, comfort, and sense of place. The integration of sustainability, tropical design, and user experience demonstrates that urban cafés can function as environmentally responsive public spaces. This study contributes to architectural discourse by highlighting the potential of café design as a medium for sustainable and climate-adaptive architecture in tropical urban contexts.